2017
DOI: 10.18287/2412-6179-2017-41-4-588-591
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Implementation of a Multi-View Image Segmentation Algorithm Using the Hough Transform

Abstract: We report on the parallel implementation of a multi-view image segmentation algorithm via segmenting the corresponding three-dimensional scene. The algorithm includes the reconstruction of a three-dimensional scene model in the form of a point cloud, and the segmentation of the resulting point cloud in three-dimensional space using the Hough space. The developed parallel algorithm was implemented on graphics processing units using CUDA technology. Experiments were performed to evaluate the speedup and efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 5 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…The results of morphological processing segmentation are shown in Figure 7. The proposed method of identifying significant structures was compared with other measures that calculate the optimal structure: contrast discrimination, a combined approach to optimization [18]; quantitative indicators of changes based on the organization of functions: eigenvalues and eigenvectors [19] and stochastic areas of completion: a neural model of illusory shape of the contour and significance [20][21][22][23]. Let us consider examples of practical use of these methods in solving the problem of segmentation of important structures in the image.…”
Section: Figurementioning
confidence: 99%
“…The results of morphological processing segmentation are shown in Figure 7. The proposed method of identifying significant structures was compared with other measures that calculate the optimal structure: contrast discrimination, a combined approach to optimization [18]; quantitative indicators of changes based on the organization of functions: eigenvalues and eigenvectors [19] and stochastic areas of completion: a neural model of illusory shape of the contour and significance [20][21][22][23]. Let us consider examples of practical use of these methods in solving the problem of segmentation of important structures in the image.…”
Section: Figurementioning
confidence: 99%
“…Data from each expert has been processed and analyzed (it presented in table 5). Thus, after analyzing the assessments of all experts and calculating the average for each criterion [18], we can conclude that the piano is heard by experts to sound more realistic than the guitar. It can also be concluded that the composition generated by abstract images is more pleasant by ear than generation by landscape.…”
Section: The Experiments Of Evaluating Of the Quality Of Generated Soundsmentioning
confidence: 99%